Sap flux density measurements based on the heat field deformation method - Nadezhdina, Nadezhda; Vandegehuchte, Maurits W; Steppe, Kathy (Trees, 2012)
Accurate measurements of whole tree water use are needed in many scientiﬁc disciplines such as hydrology, ecophysiology, ecology, forestry, agronomy and climatology. Several techniques based on heat dissipation have been developed for this purpose. One of the latest developed techniques is the heat ﬁeld deformation (HFD) method, which relies on continuous heating and the combination of a symmetrical and an asymmetrical temperature measurement. However, thus far the development of this method has not been fully described in the scientiﬁc literature. An understanding of its underlying principles is nevertheless essential to fully exploit the potential of this method as well as to better understand the results. This paper therefore structures the existing, but dispersed, data on the HFD method and explains its evolution from an initial ratio of temperature differences proportional to vapor pressure deﬁcit to a fully operational and practically applicable sap ﬂux density measurement system. It stresses the importance of HFD as a method that is capable of measuring low, high and reverse ﬂows without necessitating zero ﬂow conditions and on several sapwood depths to establish a radial proﬁle. The combination of these features has not been included yet in other heat-based sap ﬂow measurement systems, making the HFD method unique of its kind.
Keywords: Flow direction; Radial proﬁle; Sensor; Thermal gradient; tree water use